Injury, intense dust exposure, and chronic disease among survivors of the World Trade Center terrorist attacks of September 11, 2001 - Howard E. Alper; Shengchao Yu; Steven D. Stellman; Robert M. Brackbill (BMC, 2017)
Abstract Background The World Trade Center attack of September 11, 2001 in New York City (9/11) exposed thousands of people to intense concentrations of hazardous materials that have resulted in reports of increased levels of asthma, heart disease, diabetes, and other chronic diseases along with psychological illnesses such as post-traumatic stress disorder (PTSD). Few studies have discriminated between health consequences of immediate (short-term or acute) intense exposures versus chronic residential or workplace exposures. Methods We used proportional hazards methods to determine adjusted hazard ratios (AHRs) for associations between several components of acute exposures (e.g., injury, immersion in the dust cloud) and four chronic disease outcomes: asthma, other non-neoplastic lung diseases, cardiovascular disease, and diabetes, in 8701 persons free of those conditions prior to exposure and who were physically present during or immediately after the World Trade Center attacks. Participants were followed prospectively up to 11 years post-9/11. Results Heart disease exhibited a dose-response association with sustaining injury (1 injury type: AHR =2.0, 95% CI (Confidence Interval) 1.1-3.6; 2 injury types: AHR = 3.1, 95% CI 1.2-7.9; 3 or more injury types: AHR = 6.8, 95% CI 2.0-22.6), while asthma and other lung diseases were both significantly associated with dust cloud exposure (AHR = 1.3, 95% CI 1.0-1.6). Diabetes was not associated with any of the predictors assessed in this study. Conclusion In this study we demonstrated that the acute exposures of injury and dust cloud that were sustained on 9/11/2001 had significant associations with later heart and respiratory diseases. Continued monitoring of 9/11 exposed persons' health by medical providers is warranted for the foreseeable future.